PEMANFAATAN RUMPUT GAJAH (PENNISETUM PURPUREUM) SEBAGAI BAHAN BAKU KERTAS SENI DENGAN PENAMBAHAN KONSENTRASI Na2co3 DAN PEWARNA YANG BERBEDA - Sanastri, Enggar Rosmita (AGRONIMAL: Jurnal Ilmiah Pertanian dan Peternakan, 2025)
Elephant grass (Pennisetum purpureum) is commonly utilized as animal feed; therefore, alternative applications with higher added value are needed. Elephant grass contains cellulose that can be used as a raw material for handmade paper production. This study aimed to determine the tensile strength, tear resistance, and organoleptic characteristics of art paper produced from elephant grass with different concentrations of Na₂CO₃ and natural dyes. The research employed an experimental method using a Completely Randomized Design (CRD) with two treatment factors. Factor A was Na₂CO₃ concentration: A1 (10%), A2 (12.5%), and A3 (15%). Factor B was natural dye type: B1 (pandan leaf) and B2 (mangosteen peel), with each treatment replicated twice. Data collection was conducted using descriptive qualitative analysis. The results showed that the highest tensile strength was obtained in treatment A3B1 (15% Na₂CO₃ with pandan leaf dye), reaching 19.7038 N, while the highest tear resistance was observed in treatment A3B2 (15% Na₂CO₃ with mangosteen peel dye), reaching 16.3454 N. Organoleptic evaluation indicated that the best texture and fiber appearance were found in treatment A1B2, while the most preferred color and overall acceptability were achieved in treatment A2B1. These findings demonstrate that elephant grass has strong potential as an environmentally friendly raw material for art paper through appropriate alkali concentration and natural dye variation.